Prenatal immune challenge in rats: Altered responses to dopaminergic and glutamatergic agents, prepulse inhibition of acoustic startle, and reduced route-based learning as a function of maternal body weight gain after prenatal exposure to Poly IC - Vorhees, Charles V. (2012)
Prenatal maternal immune activation has been used to test the neurodevelopmental hypothesis of schizophrenia. Most of the data are in mouse models; far less is available for rats. We previously showed that maternal weight change in response to the immune activator polyinosinic-polycytidylic (Poly IC) in rats differentially affects offspring. Therefore, we treated gravid Harlan Sprague-Dawley rats i.p. on embryonic day 14 with 8 mg/kg of Poly IC or Saline. The Poly IC group was divided into those that lost or gained the least weight, Poly IC (L), versus those that gained the most weight, Poly IC (H), following treatment. The study design controlled for litter size, litter sampling, sex distribution, and test experience. We found no effects of Poly IC on elevated zero-maze, open-field activity, object burying, light-dark test, straight channel swimming, Morris water maze spatial acquisition, reversal, or shift navigation or spatial working or reference memory, or conditioned contextual or cued fear or latent inhibition. The Poly IC (H) group showed a significant decrease in the rate of route-based learning when visible cues unavailable in the Cincinnati water maze and reduced prepulse inhibition of acoustic startle in females, but not males. The Poly IC (L) group exhibited altered responses to acute pharmacological challenges: exaggerated hyperactivity in response to (+)-amphetamine and an attenuated hyperactivity in response to MK-801. This model did not exhibit the cognitive, acoustic startle, or latent inhibition deficits reported in Poly IC-treated rats, but showed changes in response to drugs acting on neurotransmitter systems implicated in the pathophysiology of schizophrenia (dopaminergic hyperfunction and glutamatergic hypofunction).